Integrated MicroRNA–mRNA Analyses of Distinct Expression Profiles in Hyperoxia-Induced Bronchopulmonary Dysplasia in Neonatal Mice - Wang, Chengqiang; Zhang, Sheng; Zhu, Lina; Duan, Jun; Huang, Bo; Zhang, Xiaoying (American Journal of Perinatology, 2021)
Objective Bronchopulmonary dysplasia (BPD) is a common chronic lung disease of preterm neonates; the underlying pathogenesis is not fully understood. Recent studies suggested microRNAs (miRNAs) may be involved in BPD.Study Design miRNA and mRNA microarrays were performed to analyze the expression profiles of miRNA and mRNA in BPD and control lung tissues after oxygen and air exposure on day 21. Bioinformatics methods, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), were performed to predict the potential functions of differentially expressed genes. Then, miRNA–mRNA regulatory network was constructed by protein–protein interaction (PPI) data and TarBase data.Results Our results showed that a total of 192 differentially expressed miRNAs (74 downregulated and 118 upregulated) and 1,225 differentially expressed mRNAs (479 downregulated and 746 upregulated) were identified between BPD mice and normoxia-control mice. GO and KEGG analysis showed that for downregulated genes, the top significant enriched GO terms and KEGG pathways were both mainly related to immune and inflammation processes; for upregulated genes, the top significant enriched GO terms and KEGG pathways were both mainly related to extracellular matrix (ECM) remodeling. PPI network and miRNA–mRNA regulatory network construction revealed that the key genes and pathways associated with inflammation and immune regulation.Conclusion Our findings revealed the integrated miRNA–mRNA data of distinct expression profiles in hyperoxia-induced BPD mice, and may provide some clues of the potential biomarkers for BPD, and provide novel insights into the development of new promising biomarkers for the treatment of BPD.Key Points
Keywords: bronchopulmonary dysplasia; preterm infant; hyperoxia; microRNA; bioinformatics; immune regulation